2016
DOI: 10.2196/jmir.5598
|View full text |Cite
|
Sign up to set email alerts
|

Depression Screening Using Daily Mental-Health Ratings from a Smartphone Application for Breast Cancer Patients

Abstract: BackgroundMobile mental-health trackers are mobile phone apps that gather self-reported mental-health ratings from users. They have received great attention from clinicians as tools to screen for depression in individual patients. While several apps that ask simple questions using face emoticons have been developed, there has been no study examining the validity of their screening performance.ObjectiveIn this study, we (1) evaluate the potential of a mobile mental-health tracker that uses three daily mental-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
133
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(137 citation statements)
references
References 51 publications
1
133
0
3
Order By: Relevance
“…Based on titles and abstracts, 18 records were selected for full text screening; 13 out of these 18 [ 29 - 41 ] being discarded for various reasons (see Multimedia Appendix 1 ). A total of 5 publications [ 42 - 46 ] were finally included. An interrater agreement of kappa=.561 was found, reaching a moderate agreement according to Landis and Koch [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on titles and abstracts, 18 records were selected for full text screening; 13 out of these 18 [ 29 - 41 ] being discarded for various reasons (see Multimedia Appendix 1 ). A total of 5 publications [ 42 - 46 ] were finally included. An interrater agreement of kappa=.561 was found, reaching a moderate agreement according to Landis and Koch [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 5 studies included a total of 644 patients, mean age 52.16 years (sample sizes and mean ages listed in Table 1 ). Of these, 3 studies were conducted in Korea [ 42 , 44 , 46 ], 1 in the United States [ 43 ], and 1 in Sweden [ 45 ]. All main authors affiliations were university departments [ 42 - 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Systematic reviews have summarized the therapeutic effects of technology mediated mental health information systems [15]. For example, mental health apps on mobile phones could improve the accessibility to treatment and facilitate proactive seeking for professional help [13,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have summarized therapeutic effects of technology mediated mental health information systems [16]. For example, reviews of the efficacy of mental health apps on mobile devices reported that mobile health apps had the potential to improve accessibility to seek treatment [17,19]. In comparison, our work represents the first effort towards designing and developing mobile behavioral sensing technology with the objective of enhancing the efficiency, accessibility, and scalability of mental health services at university counseling centers.…”
Section: Related Workmentioning
confidence: 99%